Comparative Analysis of Gradient-Based Optimizers in Feedforward Neural Networks for Titanic Survival Prediction - Adi Pratama, I Putu; Ni Wayan Jeri Kusuma Dewi (yocto brain, 2025)
Introduction: Feedforward Neural Networks (FNNs), or Multilayer Perceptrons (MLPs), are widely recognized for their capacity to model complex nonlinear relationships. This study aims to evaluate the performance of various gradient-based optimization algorithms in training FNNs for Titanic survival prediction, a binary classification task on structured tabular data. Methods: The Titanic dataset consisting of 891 passenger records was pre-processed via feature selection, encoding, and normalization. Three FNN architectures—small ([64, 32, 16]), medium ([128, 64, 32]), and large ([256, 128, 64])—were trained using eight gradient-based optimizers: BGD, SGD, Mini-Batch GD, NAG, Heavy Ball, Adam, RMSprop, and Nadam. Regularization techniques such as dropout and L2 penalty, along with batch normalization and Leaky ReLU activation, were applied. Training was conducted with and without a dynamic learning rate scheduler, and model performance was evaluated using accuracy, precision, recall, F1-score, and cross-entropy loss. Results: The Adam optimizer combined with the medium architecture achieved the highest accuracy of 82.68% and an F1-score of 0.77 when using a learning rate scheduler. RMSprop and Nadam also performed competitively. Models without learning rate schedulers generally showed reduced performance and slower convergence. Smaller architectures trained faster but yielded lower accuracy, while larger architectures offered marginal gains at the cost of computational efficiency. Conclusions: Adam demonstrated superior performance among the tested optimizers, especially when coupled with learning rate scheduling. These findings highlight the importance of optimizer choice and learning rate adaptation in enhancing FNN performance on tabular datasets. Future research should explore additional architectures and optimization strategies for broader generalizability